Analisis Faktor-Faktor Yang Mempengaruhi Perkembangan Usaha Pada Pelaku UMKM Kota Salatiga - ZAENURI, AHMAD; ZUSRONY, EDWIN; NURCAHYANINGSIH, WIDYA (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This study wants to see the effect of entrepreneurial characteristics, quality of human resources, and marketing strategies on business development, in this case MSMEs in the city of Salatiga, Central Java. This study uses a quantitative approach with multiple linear regression analysis method. The population is SMEs in the city of Salatiga and obtained 60 respondents with a sampling technique using purposive sampling. The results of the partial test showed that all independent variables had a significant effect on the dependent variable with a significance above 0.005. The contribution of the entrepreneurial characteristics variable, the quality of human resources, and the marketing strategy based on the simultaneous test is 75% of the business development variable (Y). Characteristics of entrepreneurs is the independent variable that most dominantly affects the dependent variable with a t-count value of 4.217.